2020
DOI: 10.1210/clinem/dgaa398
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the GH/IGF-I Axis and Gut Microbiome after Traumatic Brain Injury: A New Clinical Syndrome?

Abstract: Context Pituitary dysfunction with abnormal GH secretion and neurocognitive deficits are common consequences of traumatic brain injury (TBI). Recognizing the comorbidity of these symptoms is of clinical importance; however, efficacious treatment is currently lacking. Evidence Acquisition A review of studies in PubMed published between January 1980 to March 2020 and ongoing clinical trials was conducted using the search terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 104 publications
0
17
0
1
Order By: Relevance
“…This is consistent with another study that found a reduction in bone formation rate and a reduction in bone mass following RmTBI in 10-week-old female mice ( Kesavan et al, 2017 ). Dysregulated bone development following RmTBI occurs in response to disruptions in the GH/IGF-1 axis ( Kesavan et al, 2017 ; Yuen et al, 2020 ). IGF-1 which acts downstream of GH, is responsible for the anabolic processes of growth and development throughout life ( Wrigley et al, 2017 ), particularly longitudinal bone growth ( Olson et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with another study that found a reduction in bone formation rate and a reduction in bone mass following RmTBI in 10-week-old female mice ( Kesavan et al, 2017 ). Dysregulated bone development following RmTBI occurs in response to disruptions in the GH/IGF-1 axis ( Kesavan et al, 2017 ; Yuen et al, 2020 ). IGF-1 which acts downstream of GH, is responsible for the anabolic processes of growth and development throughout life ( Wrigley et al, 2017 ), particularly longitudinal bone growth ( Olson et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dysbiosis worsens and shifts toward more pathogenic microbiota with longer ICU duration [80][81][82][83]. This has also been demonstrated in neurocritical care populations, including animal and human models of TBI and spinal cord injury [84][85][86]. It has been suggested that serial changes in the ratios of beneficial species of Firmicutes/Bacteroidetes can potentially predict patient outcomes [80].…”
Section: The Microbiome and The Gut-brain Axis-implications Relating mentioning
confidence: 92%
“…Regulation of IGF transport and uptake-related proteins were the most important interacting protein classes that were presented both in group 1d/C and 7d/C of DEPs (Supplementary Figure S4), suggesting it may serve as a therapeutic target for early injury and late restoration. Recent research shows that growth hormone (GH) and IGF de ciency after TBI may inhibit the recovery of the axon and neurons, and thus GH/IGF-I system would be bene t for the therapy of TBI [17][18][19] .…”
Section: Neuron Projection and Recoverymentioning
confidence: 99%